2021
DOI: 10.1002/lary.29853
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Cochlear Implantation in Childhood Unilateral Hearing Loss (CUHL Trial)

Abstract: Objectives/Hypotheses: Children with unilateral sensory hearing loss (UHL) struggle to understand speech in noise and locate the origin of sound and have reduced quality of hearing. This clinical trial will determine the benefits of cochlear implantation in children with UHL.Study Design: Prospective clinical trial. Methods: Twenty children with at least moderate to profound sensory hearing loss and poor speech perception (word score <30%) in one ear and normal hearing in the contralateral ear participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 113 publications
6
64
0
3
Order By: Relevance
“…Findings also reveal that consistent cochlear implant use can partially reverse these cortical effects of SSD in children [68]. A recent controlled prospective longitudinal clinical trial revealed substantial benefits of cochlear implant for SSD, with subjects showing rapid improvements in speech perception in quiet, and consistent improvements in masked speech perception and sound localization [15 ▪▪ ]. Subjects not only demonstrated a head shadow benefit, but also demonstrated a significant summation effect and squelch benefit [15 ▪▪ ].…”
Section: Impact Of Unilateral Hearing Loss In Childhoodmentioning
confidence: 89%
See 3 more Smart Citations
“…Findings also reveal that consistent cochlear implant use can partially reverse these cortical effects of SSD in children [68]. A recent controlled prospective longitudinal clinical trial revealed substantial benefits of cochlear implant for SSD, with subjects showing rapid improvements in speech perception in quiet, and consistent improvements in masked speech perception and sound localization [15 ▪▪ ]. Subjects not only demonstrated a head shadow benefit, but also demonstrated a significant summation effect and squelch benefit [15 ▪▪ ].…”
Section: Impact Of Unilateral Hearing Loss In Childhoodmentioning
confidence: 89%
“…A recent controlled prospective longitudinal clinical trial revealed substantial benefits of cochlear implant for SSD, with subjects showing rapid improvements in speech perception in quiet, and consistent improvements in masked speech perception and sound localization [15 ▪▪ ]. Subjects not only demonstrated a head shadow benefit, but also demonstrated a significant summation effect and squelch benefit [15 ▪▪ ]. These latter findings have not been consistently observed in adult cochlear implant patients, and may reflect the increased cognitive plasticity in children, enabling them to more rapidly integrate binaural cues to improve speech perception in noise.…”
Section: Impact Of Unilateral Hearing Loss In Childhoodmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several recent original studies of cochlear implant use for children and adults with UHL/AHL. For children with UHL, Brown et al [22 ▪ ] reported the outcomes over the first 12 months of cochlear implant use for participants in the Children with UHL trial (CUHL Trial), a prospective FDA-approved clinical trial with repeated measures of monaural and binaural hearing abilities. With the cochlear implant alone, participants experienced significant improvements for speech recognition with CNC words at 3 months post-activation, reaching apparent asymptote at the 9-month interval.…”
Section: New Case Seriesmentioning
confidence: 99%